The development of communicative competence in Dominican university students, through the social network Facebook: A case study - Leonard Ruiz, Mayra (2024)
The teaching-learning process has been approached, during the last decades, from a Competency Model. These should be developed in each subject and from practice. Social networks have proved to be a feasible alternative that, with the teacher as a facilitating agent, can help students to develop their competencies. The objective of this study was to analyze the impact of the use of the social network Facebook on the development of communicative competence in Dominican university students in the area of Social Sciences. A case study, a field work, descriptive and explanatory, with a mixed, cross-sectional approach, was carried out during the May-August 2022 term, under a non-experimental design. The sample consisted of 81 students of Social Sciences subjects of the Instituto de Formación Docente Salomé Ureña of the Dominican Republic. The results obtained through the application of a questionnaire and an observation sheet, conclude that the students experienced significant improvements in aspects related to communicative competence, such as spelling, organization and coherence of their ideas, and the adoption of the habit of reviewing their writings before publishing them on Facebook. The 81 students who participated evaluated the use of Facebook as an excellent and useful tool for the teaching-learning process, and highlighted its contribution to the improvement of communicative competence. The results obtained support the statements of several authors about the usefulness of the social network Facebook in the teaching-learning process by competencies.